The Paradox of Economic Growth: How Unequal Income Distribution Triggers Social Vulnerability - Sarmiati (Journal of Economics and Social Sciences (JESS), 2026)
This study aims to analyze the phenomenon of the "Economic Growth Paradox," wherein impressive Gross Domestic Product (GDP) growth concurrently coexists with a widening disparity in income distribution that triggers social vulnerability. Utilizing a qualitative approach with a descriptive-analytical design, this research conducts an in-depth exploration of non-numerical social realities through a systematic library research and content analysis of various policy documents and strategic reports from multilateral institutions. The findings identify a state of "systemic fragility" operating through three main transmission channels: (1) social psychology, through the erosion of social cohesion and spatial segregation; (2) behavioral economics, in the form of increased crime rates as an adaptation to relative deprivation in the digital era; and (3) political legitimacy, which fuels the rise of populism due to public distrust in state institutions. The novelty of this study lies in the integration of digital lifestyle pressure variables to explain the dynamics of contemporary social vulnerability. This study concludes that national stability no longer depends solely on the quantity of economic growth, but rather on the quality of inclusiveness in economic access distribution, which is capable of reweaving the torn social capital